Fecal examinations of dogs and cats rescued and adopted from the flood in Porto Alegre, Rio Grande do Sul, Brazil - Marques, Sandra Márcia Tietz (2025)
The objective of this work is to report gastrointestinal parasitism in dogs and cats abandoned during the May 2024 flood, rescued and adopted in Porto Alegre, Rio Grande do Sul, Brazil. From June to October 2024, fecal samples from 93 pets (15 dogs and 78 cats) were analyzed using five parasitological techniques. Of the total number of pets (15 dogs and 78 cats), the frequencies of positive samples were 46.6% (7/15) and 43.6% (34/78), respectively, for dogs and cats. The parasites present in dogs were: Ancylostoma caninum (Ercolani 1859), Trichuris vulpis (Frolich 1789), Cystoisospora felis (Wenyon, 1923; Frenkel 1977), and Toxocara canis (Werner, 1782); in cats, they were: T. canis, C. felis, Giardia sp., larvae of Aelurostrongylus abstrusus (Railliet, 1898) and Strongyloides sp., A. caninum, Dipylidium caninum (Linnaeus, 1758), and Dioctophyma renale (Goeze, 1782). Th ese results demonstrate the importance of parasitological diagnosis based on the identifi cation of parasites that can aff ect not only animal health, but also human health.